Взаємодія органів публічної влади та інститутів громадянського суспільства: стан та перспективи розвитку - Бондарчук, Наталія Володимирівна; Bondarchuk, Nataliia (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
У статті розглянуто сучасний стан взаємодії органів публічної влади і громадянського суспільства та окреслено основні перспективи їх подальшої взаємодії. Встановлено, що розвиток громадянського суспільства має вирішальне значення для встановлення та функціонування демократії в державі. Саме тому заохочення активної співпраці між громадським суспільством і органами публічної влади сприятиме створенню більш відкритого, демократичного та ефективного суспільства. Визначено, що взаємодія між владою та суспільством будується надвох важливих складових: 1) реалізації принципів демократії, прозорості та відкритості вд іяльності органів влади; 2) забезпечення можливості безпосередньої участі представників суспільства в процессах управління та вирішенні питань, які мають важливий характер. Основними проблемами розвитку взаємодії органів публічної влади та громадянського суспільства є наступні: обмеження основних прав і свобод, обмеження доступу до інформації, обмеження зібрань і масовихзаходів, зменшення фінансування тощо. Основними перспективами розвитку зазначено наступні: подальші реформи публічного управління в Україні, забезпечення підтримки громадянського суспільства через фінансову та юридичну підтримку, створення ефективних механізмів контролю за фінансами, продовження активної співпраці з міжнародними інституціями для проведення подальших реформ. The article examines the current state of interaction between public authorities and civil society and outlines the main prospects for their further interaction. It has been established that the development of civil society is of crucial importance for the establishment and functioning of democracy in the state. That is why encouraging active cooperation between civil society and public authorities will contribute to the creation of a more open, democratic and efficient society. It was determined that the interaction between the government and society is based on two important components, namely: the implementation of the principles of democracy, transparency and openness in the activities of government bodies; ensuring the possibility of direct participation of society representatives in management processes and solving issues of an important nature. It should be taken into account the multifaceted nature of interaction between citizens and the authorities through the mechanisms of civil society, which penetrates into all aspects of social and political life. Therefore, both sides should show interest in the development of civil society. The main principles of interaction between public authorities and civil society institutions are: legality; independence; openness and collegiality; responsibility; equality of rights; control. The main problems in the development of interaction between public authorities and civil society are the following: restrictions on basic rights and freedoms, restrictions on access to information, restrictions on gatherings and mass events, reduction in funding, etc. It has been established that many developments and possibilities of tools of public participation in the formation of state policy are limited and impossible due to military aggression from the side of Russia. The imposed state of war on the territory of Ukraine limited and sometimes completely changed the activity profile of civil society institutions in favor of solving war issues. In addition, the presence of access to public information, as well as the limitation of public participation projects, is observed. The following are the main prospects for development: further reforms of public administration in Ukraine, ensuring support of civil society through financial and legal support, creation of effective financial control mechanisms, continuation of active cooperation with international institutions for further reforms.
Interaction between public government bodies and civil society institutions: status and development prospects
Keywords: органи публічної влади; public authorities; взаємодія; interaction; інститути громадянського суспільства; institutions of civil society; громадська активність; public activity